A study of oral cavity lesions in a tertiary care industrial hospital - Sahoo, Soumick Ranjan; Nayak, Pallavi; Datta, Nilanjan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Oral cavity lesions can be classified as non-malignant, premalignant and malignant lesions. Diagnosis is confirmed and established by clinical evaluation, biopsy and histopathology. Very few studies have been reported in industrial hospitals. The main aim of the study was to report the various non-malignant, premalignant and malignant oral lesions in our setup. It was a retrospective study conducted at IISCO Steel Plant, Burnpur Hospital. Data of oral lesion patients in whom biopsies conducted followed by histopathology were collected from the hospital records. Various non-malignant lesions, premalignant lesions such as leukoplakia, malignancies such as squamous cell carcinoma were reported. Most of the cases of malignancy and premalignant lesions had tobacco usage which is an occupational hazard at workplace described in literature. Few cases of premalignant lesion and malignancy had negative history of tobacco consumption. It was concluded that early diagnosis helps in accurate treatment of oral cavity lesion and secondly in premalignant oral lesions associated with tobacco usage after confirmation of diagnosis and subsequent behavioural counselling patient compliance in tobacco cessation improves.